(untitled) (Fiep Bulletin - online, 2011)
The theoretical possibility examined in this study reflects the notion that learning a complex fashion, driving can be enhanced by sensory integration intensified and strengthened in terms of brain stimulation. Sample of 21 children, between 5 and 6 years in 3 groups. Collected is data on the cortical activity related to motor performance. Descriptive statistics showed that there was some increase in amplitude of brain waves and post-training decrease of errors in groups, but the inferential statistics showed these differences not as relevant. The same occurred during the transfer compared to the acquisition. Although not significant, differences between the scores pre-and post-sensory stimulation and practice have proved positive. The same occurred during the transfer.